Eating disorder psychotherapy research - beyond the brand: Introduction to a Special Section - Tasca, Giorgio A. (2013)
Psychological interventions and research for eating disorders tend to be complex, and outcomes on average are modest. Given the frequency and severity of eating disorders, these levels of outcomes are disconcerting. Adding to the current state of research is evidence that practicing clinicians do not tend to use evidence-based psychotherapies consistently for eating disorders. This is a problem not only of dissemination and uptake of research, but also one of knowledge translation. More practice-based research, in which clinicians are equal partners in developing interventions and designing research, may be necessary in order to solve the problems of modest outcomes and low research uptake. The psychotherapy research of eating disorders in this special section presents examples of research that takes place in real-world clinical contexts with complex patients and that can be more easily translated into clinical practice.